Levantamento dos aspectos tecnológicos, econômicos, sociais, ambientais e legais da carcinicultura marinha, antes e depois da mancha branca – WSSV - Fernandes, Thaíza Lorena Barbosa (Universidade Federal Rural do Semi-Árido, 2017)
Among aquiculture activities, shrimp farming, known as carciniculture, occupies a prominent place, as these animals are considered the main commodity among products of aquatic origin. The husbandry of Brazilian shrimp is a predominant activity in the Northeast region, the most prominent states in this sector is Ceará, with 25.431 tons, followed by Rio Grande do Norte with 14.656 tons. Shrimp production in 2016 had a reduction of 25.39% compared to 2015, caused by the White Spot Virus Syndrome - WSSV, which reached the husbandries in Northeast. In Rio Grande do Norte, there was no official record of the presence of the WSSV until 2011, but there was great evidence of the presence of the disease in the South Coast region of the state, and in 2012 the disease was confirmed. In 2015, the White Spot reached the northern coast of Rio Grande do Norte, including the Mossoró region. The objective of this work aimed to evaluate the before and after of the WSSV infestation in shrimp production in the city of Mossoró, Rio Grande do Norte. The research was carried out through the application of a semi-structured questionnaire on the shrimp farms of the city. The results show the registration of 37 farms, 32 producers and a total area of water line to shrimp husbandry with 730.6 hectares. Most farms are micro (35.1%) and medium-sized (35.1%), creating a total of 148 direct jobs. All the shrimp production of Mossoró was commercialized in the national market, mainly in the northeast and southeast regions. Virtually all farms use water from wells and are licensed by the relevant environmental agencies. With the arrival of the white spot the interviewees reported a decrease in production of approximately 80%, since the production was on average 2.3 tons / hectare / cycle of shrimp, in which it produced a total of 3,892.5 tons / hectare / year and are currently taking on average only 0.5 tonnes / hectare / cycle, reaching a production of 1,160.1 tonnes / hectare / year, but due to the good price of shrimp at the moment and alternative productions such as polyculture and greenhouses can keep in activity.
Monografia
Keywords: Carcinicultura; Censo; Mancha Branca; CIENCIAS AGRARIAS::RECURSOS PESQUEIROS E ENGENHARIA DE PESCA